Estimation of genetic parameters for growth traits in Baluchi sheep using Gompertz growth curve function - Saghi, D A; Aslaminejad, A; Tahmooresepur, M; Frahangfar, H; Nassiri, M; Dashab, G R (The Indian Journal of Animal Sciences, 2012)
Gompertz growth curve function was fitted to monthly live weight records (from birth to yearling) of Baluchi lambs. The data were from 7861 animals from 2 flocks. The growth curve parameters derived from the function for individual were used in estimation of genetic parameters. Least squares means for growth parameters of A (asymptomatic mature weight), B (maximum growth rate) and C (days in maximum growth rate) were 37.23(kg), 0.216(kg) and 48.30(days), respectively. The coefficient of determination and live weight at point of inflation were 0.99 and 13.7 kg, respectively. Year of birth, sex, type of birth and age of dam were significant sources of variation in growth curve parameters. Correlations of cross validation data indicated that multiple traits model produced higher accuracy in estimation of growth curve parameters. Heritability estimates for A, B and C were 0.3, 0.18 and 0.1, respectively. Genetic correlations between A and B and A and C were 0.86, 0.21, respectively. Genetic correlations between A, B, C and body weight at different ages were ranged between (0.43 to 0.98), (0.58 to 0.89) and (–0.59 to 0.30), respectively. There was a potential in genetic changes of growth pattern in Baluchi sheep. The 6 month weight in which lambs are less influenced by maternal effects and there are high genetic correlations between parameters, is one of desirable criteria selection to change growth pattern in Iranian Baluchi sheep.